Stereocomplex micelle efficiently transports Doxorubicin for enhanced lymphoma suppression in vivo. Issue 17 (21st November 2016) - Feng, Tao; Xiao, Zhongping; Geng, Li; Gao, Peng; Fu, Kun; Li, Zhibo
Abstract: The application of Doxorubicin (DOX) in the chemotherapy for lymphoma is seriously hampered by the side effects of DOX, especially the cardiotoxicity and nephrotoxicity. Nanoscale micelle as a promising drug delivery system has gained more and more interest in malignancy chemotherapy. In this study, we successfully fabricated DOX-loaded stereocomplex micelle (SCM/DOX) from the equimolar mixture of the enantiomeric four-armed poly(ethylene glycol)-polylactide (PDM and PLM) copolymers. The SCM/DOX showed proper hydrodynamic size of ~90 nm and slow DOX release in phosphate-buffered saline at pH 7.4. The antitumor activities of DOX, PDM/DOX, PLM/DOX, and SCM/DOX toward lymphoma cells were tested in vitro and in vivo . Our data demonstrated that the SCM/DOX more effectively inhibited the cell proliferation than PDM/DOX, PLM/DOX, and free DOX in vitro . In the in vivo antitumor test, the SCM/DOX more effectively inhibited the growth of EL4 lymphoma, too. In addition, the body weight loss caused by SCM/DOX was alleviated than DOX. More importantly, the cardiotoxicity, nephrotoxicity, and hepatotoxicity caused by DOX in mice were obviously attenuated compared to the free DOX treatment group. Taken together, all the results indicated that the SCM/DOX could inhibit the growth of EL4 lymphoma cells and attenuate the toxicity of DOX more efficiently, which suggested SCM/DOX was promising for the prevention and treatment of lymphoma.